Efektivitas Media Komik Berbasis Kearifan Lokal dalam Keterampilan Menulis Narasi Siswa Kelas III di UPT SPF SD Inpres Minasa Upa - Nuramanah Nuramanah; Abd Rahman Rahim; Anzar Anzar (Lembaga Yasin AlSys, 2025)
The limited number of studies on the effectiveness of local wisdom-based comic media in improving students’ narrative writing skills forms the background of this research, despite its significant impact on the quality of Indonesian language instruction in elementary schools. This study aims to examine the effectiveness of using comic media based on local wisdom in enhancing the narrative writing skills of third-grade students at UPT SPF SD Inpres Minasa Upa. A quantitative method with a true experimental design was employed, involving 48 students selected from a population of 73 using random sampling techniques. Data were collected through narrative writing skill tests and student activity observation sheets, and analyzed using both descriptive statistics (mean, percentage, and standard deviation) and inferential statistics via the Independent Samples t-Test. The results show that local wisdom-based comic media is effective in improving narrative writing skills, as indicated by the experimental group’s posttest mean score of 19.46 (equivalent to 84.61), which was higher than the control group's score of 17.46 (equivalent to 79.36). The t-test yielded a value of t = 2.860 with sig. (2-tailed) = 0.006 < 0.05, thus supporting the alternative hypothesis. The main conclusion of this study is that comic media rooted in local wisdom is proven effective in enhancing students' narrative writing skills. The implications include theoretical contributions to the study of culturally based learning media and practical recommendations for teachers to develop engaging, contextual teaching tools. The study also opens avenues for future research on other language skills using similar approaches.